2021
DOI: 10.3390/jcm11010197
|View full text |Cite
|
Sign up to set email alerts
|

Optical Coherence Tomography Angiography in Type 1 Diabetes Mellitus—Report 2: Diabetic Kidney Disease

Abstract: The purpose of this study is to investigate potential associations between optical coherence tomography angiography (OCTA) parameters and diabetic kidney disease (DKD) categories in type 1 diabetes mellitus (T1DM) patients and controls. A complete ocular and systemic examination, including OCTA imaging tests and bloods, was performed. OCTA parameters included vessel density (VD), perfusion density (PD), foveal avascular zone area (FAZa), perimeter (FAZp) and circularity (FAZc) in the superficial vascular plexu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…Cankurtaran et al [ 36 ] reported that vessel densities in the superficial capillary plexus, whole disc, and peripapillary area were significantly different depending on the presence of diabetic albuminuria, even in the absence of DR. In other studies, patients with either type 1 or type 2 DM showed a decrease in the quantitative parameters identified by OCTA in diabetic nephropathy [ 37 , 38 ]. Although our study did not evaluate OCTA quantitative parameters and simply confirmed the relationship between DR severity and diabetic nephropathy, meaningful results can be expected if such OCTA parameters are used in the analysis in future studies.…”
Section: Discussionmentioning
confidence: 90%
“…Cankurtaran et al [ 36 ] reported that vessel densities in the superficial capillary plexus, whole disc, and peripapillary area were significantly different depending on the presence of diabetic albuminuria, even in the absence of DR. In other studies, patients with either type 1 or type 2 DM showed a decrease in the quantitative parameters identified by OCTA in diabetic nephropathy [ 37 , 38 ]. Although our study did not evaluate OCTA quantitative parameters and simply confirmed the relationship between DR severity and diabetic nephropathy, meaningful results can be expected if such OCTA parameters are used in the analysis in future studies.…”
Section: Discussionmentioning
confidence: 90%
“…Alé-Chilet et al (2021) published an original report on features of OCTA that are associated with diabetic kidney disease [ 130 ]—one of the many complications of diabetes. Diabetic kidney disease usually develops 5 years after type 1 diabetes diagnosis and occurs in 20–40% of patients with diabetes.…”
Section: Resultsmentioning
confidence: 99%
“…A total of 593 individuals with retinal images corresponding to 1186 eyes and ocular and systemic data were recruited, 478 patients with type 1 DM (n = 956 eyes) and 115 healthy controls (n = 230 eyes). Systemic, ocular, and retinal images quality exclusion criteria were applied as described elsewhere 39 , 40 41 and 439 individuals (n = 726 eyes) with a complete battery of all retinal images constituted the primary dataset for analysis. To evaluate the influence of a potential bilaterality bias, a secondary analysis was conducted by randomly selecting only 1 eye per patient (1 eye/1 patient) that included 439 patients (n = 439 eyes).…”
Section: Methodsmentioning
confidence: 99%